Genetic variation in 9p21, dietary patterns, and insulin sensitivity - Mahdavi, Sara; Jenkins, David J.A.; El-Sohemy, Ahmed (Frontiers in Genetics, 2022)
Background: Single nucleotide polymorphisms in the 9p21 region have been associated with cardiovascular disease and to a lesser extent insulin sensitivity. Previous studies have focused on older populations, and few have examined the impact of gene-diet interactions. The objective of this study was to determine the interaction between dietary patterns and 9p21 genotypes on insulin sensitivity in young adults from different ethnic groups. Methods: Subjects were 1,333 participants aged 20–29 years from the Toronto Nutrigenomics and Health Study (405 men and 928 women; 776 Caucasians and 557 East Asians). Fasting blood was collected to measure glucose, insulin, c-reactive protein and serum lipids, as well as to isolate DNA for genotyping subjects for five SNPs in 9p21 (rs10757274, rs10757278, rs1333049, rs2383206, and rs4977574). Insulin resistance (HOMA-IR) and beta-cell dysfunction (HOMA-Beta) were calculated from fasting insulin and glucose concentrations. The Toronto-modified Harvard 196-item semi-quantitative food frequency questionnaire was used to measure dietary intake over 1 month and principal components analysis was used to identify three dietary patterns (Prudent, Western and Eastern). ANOVA and ANCOVA were used to examine gene-diet interactions on markers of insulin sensitivity. Results: Significant gene-diet interactions on insulin sensitivity using HOMA-IR were observed with all five SNPs, which remained significant after adjusting for covariates (p < 0.05). Among those who were homozygous for the 9p21 risk allele (rs1333049), fasting insulin was 40% higher in those who were consuming a low-prudent diet compared to those consuming a high-prudent diet (p < 0.05). No differences were observed between those following a low versus high-prudent diet among those who did not carry a 9p21 risk allele. Similar findings were observed with HOMA-Beta, however, the association was only significant for rs10757274 (p = 0.04). Conclusion: Our findings suggest that a prudent dietary pattern may protect against the effects of 9p21 risk genotypes on insulin sensitivity.